Evaluation of overexposure risk when there is a space between the subject and the couch in computed tomography: a phantom study - Fujiwara, Yuta; Kamihoriuchi, Yoshiki; Higuchi, Fumie; Nakayama, Shinichi; Ohyama, Yutako; Sasaki, Tomoko; Watanabe, Shinsaku; Masuda, Takanori (Radiological physics and technology, 2024)
The purpose of this study was to investigate the risk of overexposure associated with automatic tube current modulation (ATCM) and automatic couch height positioning compensation mechanism (AHC) in computed tomography (CT) systems, particularly in scenarios involving a gap between the subject and the couch. Results revealed that when AHC was enabled, CT dose index volume (CTDI vol ) increased by approximately 10% at 2.5 cm, 20% at 5.0 cm, and 40% at 10.0 cm gaps compared to close contact conditions. While the AHC function ensures consistent exposure doses and image quality regardless of subject positioning relative to the CT gantry isocenter, the study highlights a potential risk of overexposure when a gap exists between the subject and the couch. These findings offer valuable insights for optimizing CT imaging protocols and underscore the importance of carefully considering subject positioning in clinical practice.